Genome-wide gene expression profiles of dental follicle stem cells. (February 2014) - Vollkommer, Tobias; Gosau, Martin; Felthaus, Oliver; Reichert, Torsten E.; Morsczeck, Christian; Götz, Werner
Abstract Objective. Dental stem cells (SCs) will be increasingly used for bone regeneration in the future. Recently, dental follicle cells (DFCs) from retained human third molars have been isolated and characterized as osteogenic progenitors. Although these results are promising for regenerative dentistry, molecular processes during osteogenic differentiation are not yet well understood. Materials and methods. This study compared DFCs before and during osteogenic differentiation. ALP activity was measured and cells were stained with alizarin red. Real-time RT-PCRs for osteogenic markers were done. The genome-wide expression profile was evaluated using a microarray. Results. DFCs showed strong mineralization and increased expression of osteogenic marker genes during osteogenic differentiation. A microarray analysis showed regulated genes before and in the process of osteogenic differentiation (day 7). Several regulated genes in DFCs were associated with skeletal development. Bioinformatic analysis revealed a number of factors associated with dental follicle osteogenic differentiation. Osteogenic differentiation affected expression levels of the transcriptional regulators FOXC2 and ZNF219. Conclusion. In conclusion, the results yielded new objectives for further studies on transcription factors like FOXC2 or ETV1 and their role in dental SCs during osteogenic differentiation.